Eşit ve Farklı Varyanslı Populasyonlardan Alınan Örneklerin Ayıklanmış (Trimmed)-t Testi ile Karşılaştırmasında Gerçekleşen I.Tip Hata ve Testin Gücü - Fikret Gürbüz; Ensar Baspınar (Journal of Agricultural Sciences)
In this study, the efficiency of Trimmed-t Test was examined to compare the samples of varying sizes taken from populations with equal and unequal variances which were trimmed at different rates. The results of 10000 simulation test show that Trimmed-t Test would be used confidentially if the samples are equal in size and the population variance is not known and/or it is not homogenous.